Sexual Health and Wellbeing through the Life Course: Ensuring Sexual Health, Rights and Pleasure for All. Issue 4 (2nd October 2021) - Sladden, Tim; Philpott, Anne; Braeken, Doortje; Castellanos-Usigli, Antón; Yadav, Vithika; Christie, Emily; Gonsalves, Lianne; Mofokeng, Tlaleng
Abstract: This commentary summarizes the context and positioning of sexual health, sexual rights and sexual pleasure, as three interlinked and indivisible aspects of sexual health and wellbeing (SH&W). In turn, sexual health is a major domain within broader sexual and reproductive health and rights (SRHR), both in its own right as a human right, and owing to the importance of good sexual health for ensuring good reproductive outcomes. Furthermore, SRHR is a necessary, core part of overall health, thus sexual health and wellbeing is a fundamental aspect of general health that is often overlooked or even denied for some. In this commentary, we utilize a life course approach to illustrate how the tripartite of sexual health, rights and pleasure manifest themselves with different interlocking linkages, and actively contribute to overall health throughout life. As other papers in this series attest, the linkages of pleasure with the right to and attainment of health has received inadequate attention to date, both within the scientific literature and in policy narratives.